Faktor yang Memengaruhi Pemanfaatan Pelayanan Kesehatan di Wilayah Kerja Puskesmas Lengkosambi Tahun 2024 - Maria Teresia E. Pora Abo; Rina Waty Sirait; Masrida Sinaga (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
One of the efforts to improve the health status of the community is to encourage the utilization of health services. The number of patient visits at Lengkosambi Health Center fluctuates from 2021 to 2023, reflecting the influence of various factors such as predispositions, enablers, and needs in determining health service utilization. One factor that influences the utilization of these services is the community's perception of illness. People may feel healthy and do not need regular check-ups or treatment, even though they have unrecognized health risks. This study aims to determine the factors that influence health service utilization in the working area of Lengkosambi Health Center in 2024. This was an analytic survey study with a cross-sectional design. The study population consisted of 5,023 people with a sample of 95 people selected through simple random sampling technique. Data were collected using a questionnaire and analyzed by univariate analysis and bivariate analysis using the chi-square test. The results showed that insurance ownership (p=0.002), availability of health workers (p=0.003), and perception of illness (p=0.005) had a significant influence on the utilization of health services at Lengkosambi Health Center. In contrast, accessibility (p=0.163) did not show a significant effect. Therefore, health workers at health center are advised to increase education to the community regarding the correct concept of health and illness and the importance of utilizing health services, even for complaints that are considered mild.